Ammonium perchlorate encapsulating nanothermites as high energetic composites: Preparation, thermal decomposition and combustion properties. (2nd November 2019) - Hu, Yinghui; Yang, Yulin; Lin, Kaifeng; Hao, Dongyu; Qiu, Lele; Wang, Dakang; Fan, Ruiqing; Xia, Debin
Graphical abstract: Highlights: EISA method was developed to encapsulate various nanothermites into AP. nAl/nCuO/AP showed excellent AP decomposition and combustion performance. More intimate interaction between AP and nanothermites. Less agglomeration of nanothermites. Abstract: In this study, various nanothermites, such as nCuO/nano Al (nAl), nMoO3 /nAl, nBi2 O3 /nAl, nFe2 O3 /nAl, nNiO/nAl and nMgO/nAl, were encapsulated into ammonium perchlorate (AP) by the evaporation induced self-assembly (EISA) method. The obtained composites showed superior properties in decreasing the decomposition temperature of AP, increasing heat of release and ignition and combustion properties than the corresponding physically-mixed ones. The mechanism for such high-quality composites prepared by EISA was due to not only more intimate interaction between AP and nanothermites but also less agglomeration of nanothermites. nAl/nCuO/AP showed the lowest decomposition temperature of AP, highest heat of release and best ignition and combustion properties among all the obtained composites by EISA. This was because of effective conversion of NH3 to N2 O with less NO production, as proved by the real-time FT-IR. This work demonstrated that EISA was an effective approach with high compatibility for obtaining various AP-nanothermites-based energetic materials.